‘AN IMPENDING DOOM’: RARE CASE OF RUPTURED PHEOCHROMOCYTOMA PRESENTING AS PHEOCHROMOCYTOMA CRISIS - Shah, Noor Muhammad Azlan; Kannan, Prashanya; Helena, Nadia; Noriza, Dian; Hanum, Fadzliana; Muthusamy, Gunavathy (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Spontaneously ruptured pheochromocytoma presenting as pheochromocytoma crisis is a rare complication and is associated with high morbidity and mortality. CASE We present a case of a 46-year-old female with left pheochromocytoma, diagnosed following a total abdominal hysterectomy for uterine leiomyoma. 24-hour urine catecholamines were elevated- norepinephrine: 2.6 x ULN [1241 nmol/L], epinephrine: 12.8 x ULN [1468.3 nmol/L], dopamine <424 nmol/L. Plasma normetanephrine and metanephrines were also elevated. CT scan showed a large adrenal mass measuring 4.98 x 5.4 x 5.5 cm. Medications were oral Prazosin 3 mg five times daily and Labetalol 100 mg twice daily. She presented four weeks later with acute onset of abdominal pain, persistent vomiting, chest discomfort, vasovagal syncope, headache and sweating. She was restless, pale and hypotensive with a BP of 80/40 mmHg and HR 104 beats per minute. Abdominal examination revealed generalised tenderness, guarding and a palpable mass over the left lower quadrant. Blood pressure increased subsequently ranging from systolic 150 to 200 mmHg and diastolic 90 to 100 mmHg. ECG showed widespread deep T inversion suggestive of Wellen syndrome with raised Troponin I (1950 ng/mL). Abdominal CT revealed a ruptured left pheochromocytoma measuring 5.0 x 6.6 x 7.1 cm with a large intra-abdominal hematoma. She was started on Prazosin 2 mg three times daily and Labetalol 100 mg three times daily for blood pressure control. She was given an insulin infusion for hyperglycemia. Packed cells were also transfused. She underwent laparotomy and adrenalectomy following adequate alpha- and betablockade. The postoperative course was uneventful. HPE of the left adrenal mass confirmed pheochromocytoma. CONCLUSION Pheochromocytoma crisis resulting from a large release of catecholamines from a ruptured pheochromocytoma is associated with high mortality. Prompt resuscitation and blood pressure control are the mainstays of treatment prior to surgical intervention.